#### Answer

The point $(-4, 3)$ is not a solution of both equations.

#### Work Step by Step

To determine whether or not the point $(-4, 3)$ is a solution of both equations, we need to substitute $4$ for $x$ and $-1$ for $y$ into both equations to see if both equations are true. Let us plug the values into the first equation to see if it is true:
$$-4 + 2(3) = 2$$
Multiply first, according to the order of operations:
$$-4 + 6 = 2$$
Let us add:
$$2 = 2$$
The point $(-4, 3)$ is a solution of the first equation.
Now, let us plug in this point into the second equation to see if the equation is true:
$$-4 - 2(3) = 6$$
Multiply first, according to order of operations:
$$-4 - (6) = 6$$
Subtract to solve:
$$-10 = 6$$
The point $(-4, 3)$ is not a solution of the second equation, so it is not a solution of both equations.